2021
DOI: 10.1002/adfm.202008400
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin‐Hyaluronan Click‐Crosslinked Cryogels Elucidate Human Macrophage Invasion Behavior

Abstract: Hydrogel models of metastasis traditionally focus on the invasion of cancer cells; however, other cells in the tumor microenvironment that are associated with metastasis also have the ability to migrate. Macrophage phenotype plays a key role in the tumor microenvironment, yet understanding their migration within tunable 3D in vitro models has been limited. To gain a greater understanding of macrophage invasive behavior, stable and transparent oxime‐crosslinked cryogels comprised of click‐crosslinked gelatin‐ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…It was likely that the macrophages might not have enough space to adhere and spread well in the MV cryogel (small pore size and low porosity), so they could not further produce strong cell pre-stress to activate the downstream signal pathways of M2 polarization. The recent studies of other types of hydrogels, including a platelet lysate-rich plasma macroporous hydrogel, 42 an amino-functionalized graphene crosslinked collagen cryogel 43 and the cryogels comprised of click-crosslinked gelatin–oxyamine and hyaluronan–aldehyde, 44 also showed that larger pore size/porosity tended to polarize macrophages toward M2 phenotype. Thus, our findings would be helpful in scaffold design to promote M2 macrophage polarization for proper healing and subsequent regeneration, which has been well proved and applied in the foreign body reaction, 45 articular cartilage defect repair, 42 and spinal cord regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…It was likely that the macrophages might not have enough space to adhere and spread well in the MV cryogel (small pore size and low porosity), so they could not further produce strong cell pre-stress to activate the downstream signal pathways of M2 polarization. The recent studies of other types of hydrogels, including a platelet lysate-rich plasma macroporous hydrogel, 42 an amino-functionalized graphene crosslinked collagen cryogel 43 and the cryogels comprised of click-crosslinked gelatin–oxyamine and hyaluronan–aldehyde, 44 also showed that larger pore size/porosity tended to polarize macrophages toward M2 phenotype. Thus, our findings would be helpful in scaffold design to promote M2 macrophage polarization for proper healing and subsequent regeneration, which has been well proved and applied in the foreign body reaction, 45 articular cartilage defect repair, 42 and spinal cord regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Adapted with permission. [ 41 ] Copyright 2022, Wiley‐VCH GmBH. d) The amount of carboxylic acid and amine functional groups in gelatin type A and type B.…”
Section: Gelatin As a Bioink For 3d Bioprintingmentioning
confidence: 99%
“…Amino acid analysis indicate that gelatin is mostly comprised of glycine (34.7%), proline (15%), alanine (13%), glutamic acid (8.6%), aspartic acid (5.2%), arginine (5.2%), and lysine (3.1%) residues (Figure 1c). [ 41 ] Due to the presence of carboxylic functional groups on aspartic acid, glutamic acid, and amine functional group on lysine, gelatin is highly amenable to chemical modifications to produce chemically cross‐linked bioinks. The carboxylic and amine groups present in gelatin are mostly used to introduce cross‐linking moieties on gelatin chains.…”
Section: Gelatin As a Bioink For 3d Bioprintingmentioning
confidence: 99%
“…Promotes wound healing [157] Synstatins (SSTN): SSTN210- Cell attachment Neurite outgrowth [158] Bone marrow mesenchymal stem cell proliferation Activates MAPK/ERK, PI3K/AKT signaling pathways [159] Enhances B16-F10 melanoma tumor growth in mice [160] Angiogenic in CAM assay and HUVEC tube forming assay [161] YIGSR Laminin β chain Inhibition of B16-F10 melanoma tumor formation in mice [162] Adhesion of cardiac myocytes to silicone but with altered physiology [163] BAEC adhesion and spreading, and inhibition of platelet adhesion onto polyurethane [164] RNIAEIIKDI Laminin γ chain Neurite outgrowth [165] THP1 macrophage adhesion [166] RRETAWA Phage display α5β1 integrin Cell attachment [167] enhance and improve pharmacokinetics (PK). For example, the discovery of the cell and tissue-penetrating neuropilin-1 binding motif R/KXXR/K, where X is any amino acid, led to the development of internalizing RGD (iRGD).…”
Section: Lama3 Lama4 Lama5 Syndecan 1-4 Heparinmentioning
confidence: 99%